Descarbonizando o campus UFSCar – Lagoa do Sino a partir da produção de biogás: uma análise de viabilidade ambiental, técnica e econômica. - Cunto, Victor Alcântara Barbosa (Universidade Federal de São Carlos, 2022)
The disposition of the organic fraction of solid waste in sanitary landfills, are responsible for environmental impacts, among them the reduction of its useful life and the generation of Greenhouse Effect Gases, besides preventing the revaluation of the waste and its economic capacity. Due to the guidelines drawn up by the National Solid Waste Policy and its environmentally appropriate destination, it is evident the relevance of the implementation of the revaluation of organic waste. Thus, this work aimed to carry out an evaluation of biogas production from organic waste from the University Restaurant at UFSCar Campus Lagoa do Sino. To achieve the main objective, a review of the literature, the technical, environmental and economic feasibility of the implementation of biodigesters was performed. Thus, the generation of 0.20 m³ day-1 of biogas was obtained, from 183.68 kg.day-1 of leftover meals. This enabled the design of an anaerobic reactor, Canadian model, with a useful volume of 4.09 m3 and initial investment of R$ 8,631.81, obtaining a return time of 1.02 years, considering the scenario of substitution of Liquefied Petroleum Gas by CH4, contributing to the feasibility of its implementation and helping to decarbonize the Lagoa do Sino Campus.
Decarbonizing the campus UFSCar - Lagoa do Sino from the production of biogas: an analysis of environmental, technical and economic viability
Keywords: Biogás; Biorreator; GLP; Bioenergia; Sustentabilidade; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA MECANICA::ENGENHARIA TERMICA::APROVEITAMENTO DA ENERGIA; ENGENHARIAS